Efficacy of palliative chemotherapy in elderly patients with colorectal cancer - Bohle, Wolfram; Pachlhofer, Amelie; Zoller, Wolfram G. (Zeitschrift für Gastroenterologie, 2019)
Background The number of old patients suffering from colorectal cancer rises. In clinical trials, old patients are underrepresented, and chemotherapy is significantly less often performed in elderly patients. We analyzed the impact of elder age for palliative chemotherapy in patients suffering from metastatic colorectal cancer, according to therapeutic drugs used, intensity of treatment performed, and therapeutic results.Materials and methods We analyzed consecutive patients with metastatic colorectal cancer treated in palliative intention in our department. Assessed data included age (</> 75 years), sex, comorbidity, site of primary tumor, k-ras-status, site and amount of metastasis, number and kind of chemotherapeutic agents used, number of consecutive therapy lines performed, dose intensity, toxicity, time between start and end of palliative chemotherapy, and overall survival. Prognostic variables were tested in uni- and multivariate analysis.Results Ninety-seven patients (69 < 75, 18 > 75 years) were included. Age groups were well balanced according to site of primary tumor, k-ras-mutational status, localization, and number of metastatic sites. Cardial and renal comorbidity was more frequent in elderly patients. The median number of chemotherapeutic drugs used and lines of therapy performed did not differ between age groups, except of oxaliplatin, which was significantly less often used in old patients. Median survival did not differ between age groups (23.4 vs. 23.5 months). In multivariate analysis, only left-sided primary tumor and more than 3 lines of therapy performed were prognostic positive variables.Conclusion Old patients can profit from palliative chemotherapy to the same extent as younger ones.
Keywords: chemotherapy; old patients; palliative therapy; colon cancer